Suture-Probe Canaloplasty as an Alternative to Canaloplasty Using the iTrack Microcatheter. Issue 9 (September 2019) - Kodomskoi, Leonid; Kotliar, Konstantin; Schröder, Andreas C.; Weiss, Michael; Hille, Konrad
Abstract : Précis: Significant intraocular pressure (IOP) reduction was achieved using a novel suture-probe canaloplasty (SPCP) procedure in patients with glaucoma. The effect and low rate of surgical complications were comparable with those of iTrack canaloplasty. Purpose: Ab externo canaloplasty using the iTrack microcatheter has been established as a safe surgical procedure to treat open-angle glaucoma. This article, however, describes the results of a novel technique using a cost-efficient suture-probe as an alternative to iTrack canaloplasty and presents 12-month follow-up results. Patients and Methods: SPCP was performed on 50 eyes of 50 patients with primary open-angle glaucoma, pseudoexfoliation glaucoma, and steroid-induced glaucoma. The mean±SD preoperative IOP was 21.9±7.0 mm Hg. A suture-probe was used to dilate Schlemm canal and to place a trabecular tensioning suture. Postoperative results were noted and statistically analyzed on the day of discharge from the clinic, and at 1.5, 3, 6, and 12 months of follow-up. Results: In all eyes, the mean postoperative IOP 12 months after SPCP was 13.7±3.0 mm Hg. The number of medications decreased from 2.8±0.9 to 0.1±0.4, and visual acuity was 0.3±0.3 logMAR . Postoperative course and complications included: hyphema >1 mm (2%); microhyphema (4%); bleb leakage (2%); bleb suture (2%); laser goniopuncture (18%); laser suture lysis (4%); scleral flap lifting (4%); and iris incarceration following laser goniopuncture (4%). Conclusions: SPCP is an inexpensive procedure that can achieve significant IOP reduction in patients with glaucoma. The IOP-lowering effect and low rate of surgical complications were very similar to those of iTrack canaloplasty.